Dyeing of Silk Fabric Using Natural Dye Extracted from Sargentodoxa Cuneata and Its Ultraviolet Resistant Property. Issue 13 (1st December 2022) - Wang, Linan; Wang, Shiwen; Song, Kaili; Yu, Zhicheng
ABSTRACT: In this research, Chinese herb Sargentodoxa cuneata was investigated as a natural dyestuff to give novel ultraviolet resistance to silk fabrics. The colorant was prepared using sodium hydroxide as extraction solvent, and the properties of the colorant were characterized using fourier transform infrared (FT-IR) and UV-vis spectrophotometric. The functionalized silk fabric was obtained by a typical dyeing process using the prepared Sargentodoxa cuneata extraction (SCE). The effects of dyeing pH, temperature, and time on dyeing properties of silk fabric were investigated. The dyed silk fabric showed excellent UV protection property as well as excellent washing durability. This investigation provides a useful strategy to develop a new class of Chinese herbs with valuable use and silk materials with functional performance.